No compelling evidence that more physically attractive young adult women have higher estradiol or progesterone. (December 2018) - Jones, Benedict C.; Hahn, Amanda C.; Fisher, Claire I.; Wang, Hongyi; Kandrik, Michal; Lao, Junpeng; Han, Chengyang; Lee, Anthony J.; Holzleitner, Iris J.; DeBruine, Lisa M.
Highlights: We investigated hormonal correlates of young adult women's physical attractiveness. Facial attractiveness changed within-women as a function of estradiol and progesterone. No evidence for the popular hypothesis that more attractive women generally have higher estradiol or progesterone. Abstract: Putative associations between sex hormones and attractive physical characteristics in women are central to many theories of human physical attractiveness and mate choice. Although such theories have become very influential, evidence that physically attractive and unattractive women have different hormonal profiles is equivocal. Consequently, we investigated hypothesized relationships between salivary estradiol and progesterone and two aspects of women's physical attractiveness that are commonly assumed to be correlated with levels of these hormones: facial attractiveness (N = 249) and waist-to-hip ratio (N = 247). Our analyses revealed no compelling evidence that women with more attractive faces or lower (i.e., more attractive) waist-to-hip ratios had higher levels of estradiol or progesterone. One analysis did suggest that women with more attractive waist-to-hip ratios had significantly higher progesterone, but the relationship was weak and the relationship not significant in other analyses. These results do not support the influential hypothesis that between-women differences in physical attractiveness are related to estradiol and/or progesterone.